Metabarcoding analysis of meiobenthic biodiversity along the Gulf of Mexico continental shelf. (31st May 2023) - Brannock, Pamela M.; Demopoulos, Amanda W.J.; Landers, Stephen C.; Waits, Damien S.; Halanych, Kenneth M.
Abstract: This study explores how diverse the meiobenthic (meiofauna and other benthic micro-eukaryotes) community is throughout the United States Gulf of Mexico (GOM) continental shelf. In late 2010 and 2011, 51 sediment samples were collected along GOM from Texas through Florida at a range of depths (40m–496m). An additional six deep-sea slope sediment cores were collected in December 2010 near the Deepwater Horizon platform (1370–1385m and 1865m). Metabarcoding of the 18S hypervariable V9 region was conducted to assess biodiversity. Within continental shelf samples, there was greater meiobenthic diversity off the Eastern GOM coast in comparison to both Central and Western GOM coast locations. The Eastern GOM coast has known sediment differences from Western GOM sites. These sediment differences along with influences from the Gulf of Mexico Loop Current may account for observed variations in GOM meiobenthic diversity. Highlights: Meiobenthic communities in the Eastern Gulf of Mexico are more diverse than Western or Central portions. Previous studies have reported difference in sediment characteristics between different GOM regions. Meiobenthic communities in the shallower Gulf of Mexico continental shelf are more diverse than deeper regions. Temperature and salinity were significantly different between the three (Western, Central, and Eastern) GOM regions. Temperature, salinity, and oxygen were significantly different in reference to water depth.